Comparative Study of 2-phase Low Frequency Triac Converter- and High Frequency Two-stage Matrix Converter Systems - Prazenica, M.; Dobrucky, B.; Benova, M.; Kassa, J. (Elektronika ir Elektrotechnika, 2010)
The paper deals with comparison of the characteristics between two-phase electronic systems: DC/AC/AC high frequency two-stage converter system made of two single-phase matrix converters with variable orthogonal output and low frequency triac converter with phase-control supplied from AC network. Low frequency triacs or thyristor converters can be innovated using switches of semiconductor device s (IGBT). Design of two-stage DC/AC/AC high frequency converter with two-phase orthogonal output using single-phase matrix converter in half-bridge connection operated with the bipolar PWM is also introduced. Ill. 17, bibl. 10 (in English; abstracts in English, Russian and Lithuanian).